Formulation of an Academic Failure Model Based on Fear of Failure and Academic Procrastination with the Mediating Role of Mindfulness - Sabalani Taleshmekaeil, Nima; Panah Ali, Amir; Badri Gargari, Rahim; Hoseini Nasab, Seyyed Davoud (International Journal of Education and Cognitive Sciences, 2025)
Purpose: The main objective of this study was to formulate a model of academic failure based on fear of failure and academic procrastination, with mindfulness as a mediating variable.Methods and Materials: The research method was structural equation modeling, consisting of four variables: fear of failure and academic procrastination as independent variables, mindfulness as the mediating variable, and academic failure as the dependent variable. The study utilized the Academic Procrastination Questionnaire by Solomon and Rothblum (1984), the Fear of Failure Scale by Conroy (2001), and the Mindfulness Questionnaire by Baer et al. (2006). The participants included 510 male and female high school students in the second cycle of secondary education in Ardabil who had experienced academic failure or were at risk of academic failure. They were selected using a purposive sampling method.Findings: The results indicated that in examining the direct effects, fear of failure and academic procrastination had a direct, negative, and significant effect on mindfulness (p = .001). Fear of failure and academic procrastination had a direct, positive, and significant effect on academic failure (p = .001). Mindfulness had a direct, negative, and significant effect on academic failure (p = .001). Moreover, in examining the indirect effects, fear of failure and academic procrastination had a positive and significant indirect effect on academic failure through the mediation of mindfulness (p = .001).Conclusion: Ultimately, the academic failure model based on fear of failure and academic procrastination, with the mediating role of mindfulness, demonstrated a good fit.